PP19 Paramedic research literature 2011–2019. A bibliographic analysis of the contents of amber, the ambulance research repository. Issue 10 (25th September 2020) - Holland, Matt; Dutton, Michelle
Abstract : Background: The data held by amber presents an opportunity to understand the structure of the published paramedic literature, specifically the output of NHS staff working in English ambulance services 2011–2019. This period is of interest because it represents part of the development phase of paramedic research in England. The authors apply a series of bibliometric measures to generate a profile of the published literature. Method: The metadata was downloaded from amber for the period from 2011–2019. The metadata was used to create a series of tables that describe the contents of amber. The data was augmented by Altmetric Scores and Citation Counts (SCOPUS) to provide a measure of the quality of the articles contained in amber. Results: The data shows a characteristic long tail with 1) Few very high scoring articles (Altmetric and Citation) and many lower scoring articles, 2) A few journals titles publish the majority of articles in paramedicine with many publishing just 1–3 articles. Altmetric scores do not predict citation counts for this data. Only six of the articles that appear in the top 20 journal articles by Altmetric score also appear in the top 20 journal articles by citation count table. Nearly 50% of article achieve an Altmetric score, only 20% of the research is cited one or more times. 68% of articles are written by more than one author including all the articles included in the top 20 article tables. Only 10 of the top 20 cited articles are published in core emergency medicine journals in this instance Resuscitation and Emergency Medicine Journal . Conclusions: Broadly, the data describes the body of research in paramedicine growing overtime in volume and quality.